The Development of Curriculum in Indonesia - Novasyari, Ressy (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
Change is an obligation to do as long as it took to change for the better and able to solve problems that arise in the past. This was the spirit of the government to create a new curriculum. Education in Indonesia makes parameters in form of curriculum that teachers should obey it in teaching and learning in the classroom. Curriculum is a guide for teachers in teaching learning process in order achieve the objective. The curriculum in language teaching and learning depends on how the organization of content. Curriculum and its development according to the needs of students, schools, communities and the demands of the times. The curriculum should be match to the dynamics and demands of society for curriculum design/program(learning) which aims to prepare students to be members of the community. This article discusses about the concept of curriculum and development of curriculum in Indonesia.